Comparative effectiveness of neuraminidase inhibitors in patients with influenza: A systematic review and network meta-analysis. Issue 2 (February 2022) - Su, Hui-Chen; Feng, I-Jung; Tang, Hung-Jen; Shih, Mei-Fen; Hua, Yi-Ming
Abstract: The aim of this study was to use a network meta-analysis (NWA) to evaluate the relative efficacy and safety of various neuraminidase inhibitors (NAIs) in reducing the duration of influenza symptoms, and thereby, informing the selection of suitable therapeutic regimens for patients with influenza. We conducted a systematic review of randomized controlled trials comparing the clinical effects of four NAIs administered to patients with influenza and placebo. Relevant studies were found in the PubMed and Cochrane databases. Unpublished studies were collected from the ClinicalTrials.gov registry and through hand searching. We carried out NWA to compare the different regimens with each other and across subgroups of age and medical status (high-risk patients). A total of 58 two-arm studies were identified. Five regimens were efficacious in reducing the time to alleviation of influenza symptoms in all populations; this efficacy was comparable. No significant improvements were seen in combination therapy groups. The mean difference in the time to alleviation of symptoms ranged from 12.78 to 19.51 h. According to the summarized mean difference and surface under the cumulative ranking curve (SUCRA), peramivir (SUCRA = 82.6%), zanamivir (SUCRA = 64%), and oseltamivir (SUCRA = 55.1%) were the three top-ranking drugs for treating influenza. Zanamivir and peramivir were the preferred pharmacologic intervention among all investigated interventions based on the calculated "value preference of SUCRA." This study is a network meta-analysis to explore the therapeutic effects of NAIs in patients with influenza. Peramivir might be the best choice for reducing the time to alleviation of symptoms.